Serum Vitamin D Status in Patients with Asthma-COPD Overlap - Khanam Rosy, Sharkia; Asaduzzaman, Md; Hassan, Samia; Bintey Mahmud, Maksuda; Sultana, Naznin; Anjum, Salma (Medicine Today, 2024)
Introduction: Asthma-COPD overlap shared its risk factors with asthma and COPD, including development in the later decades of life, airway hyper-responsiveness, often tobacco smoke exposure, and progressive loss of lung function. It has been shown that this group of patients might possess vitamin D deficiency. By assessing the level of vitamin D we can identify the deficiency earlier and can give appropriate supplements. Objective: This study was done to assess the serum vitamin D status in patients with Asthma-COPD overlap. Materials and Methods: This cross-sectional study was carried out in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University, Dhaka, from January 2018 to July 2018. Total 47 men subjects age ranged between 40-70 years were involved in this study. Among them 23 (twenty three) men (40-70 years) were involved as study group (Group II) and 24 (twenty four) men (40-70 years) were taken as control group (Group I). Results: The results were expressed as mean with standard error (mean±SEM). The data were statistically analyzed by Graphpad prism (Version 7) using independent sample ‘t’ test. The mean (±SEM) of serum vitamin D of Group I and Group II were 16.37±0.78 kg/m2 & 18.47±1.01 ng/ml respectively. Conclusion: Vitamin D deficiency is present in both groups. By this study we recommended that routine estimation of this parameter is important for early detection and prevention of complication related to Asthma-COPD overlap for managing a healthy life. Medicine Today 2024, Vol.36 (2): 120-123